Doctor's Responsibility For Actions of Delaying And Termination of Life Support of Terminal Patients During The Covid-19 Pandemi - Kusumaningrum, Anggraeni Endah (SASI, 2022)
Introduction: Medical action is a doctor's action toward a patient which includes preventive, diagnostic, curative, or rehabilitative measures. The medical action certainly brings legal consequences, so a doctor is legally responsible for the medical actions he takes, including the act of delaying and terminating life support.Purposes of the Research: This study aims to examine and analyze the responsibility of doctors for the act of delaying and terminating life support for terminal patients during the COVID-19 pandemic, as well as the obstacles and solutions.Methods of the Research: This research approach is normative juridical with secondary data as the main data obtained through literature study and will be analyzed qualitatively.Results of the Research: This study found that doctors who are negligent and guilty when performing acts of delaying and discontinuing life support can be prosecuted for criminal, civil, administrative and professional ethical responsibility. The enactment of a ministerial-level regulation that regulates this action provides legal protection for doctors, where there is a change in the way of making decisions on medical actions so that the doctor's legal responsibility turns into a collective or corporate responsibility. However, the implementation of the regulation still has various shortcomings, so legal protection for doctors is not optimal.